Aqueous Precipitation: Population Balance Modeling and Control in Multi-Cation Systems - James A. Voigt (The Minerals, Metals and Materials Society, 1996)
"The efficient separation of metal species from aqueous streams by precipitation techniques requires a fundamental understanding of the various processes that occur during precipitation. These processes include particle nucleation, particle growth by solute deposition, agglomerate formation, and agglomerate break-up. The application of the population balance approach has been used to develop a kinetic model that accounts for these competing kinetic processes. The usefulness of the model is illustrated through its application to the precipitation of yttrium hydroxynitrate, YHN. The kinetic parameters calculated from the model equations and system specific solution chemistry are used to describe several aspects of the effect of pH on the precipitation of the YHN. Implications with respect to the simultaneous precipitation of more than one cation type are also discussed through use of example systems. The effects of solution chemistry, precipitator design, and solvent choice are considered.IntroductionThe application of precipitation technologies to the separation of metals from solution is widely used. Regardless of its application, be it in such diverse areas as the preparation of metal oxide powders for use in commercial products or as a unit operation in the removal of trace metals during wastewater clean up, the fundamental processes involved are the same. These processes include: nucleation from solution, either homogeneous or heterogeneous; growth from solution with chemical reaction either in solution or at the precipitate/solution interface; growth by particle agglomeration; and particle break-up by collisional or shear forces. The effectiveness of the operation and the properties of the precipitate formed, or ""quality"" of the product, are determined by the competing kinetics of the different processes. The kinetics of the processes, in tum, are determined by system-specific solution chemistries and the conditions used to carry out the precipitation operation. For example, generally, when system conditions are such that the supersaturation driving force for precipitation is very high, growth species normally do not have the time to organize themselves with a high degree of crystallographic order and the precipitate is amorphous. In this case nucleation rates are invariably extremely high and the primary mechanism for growth is the agglomeration of nuclei. Conversely, when the supersaturation levels for the same system are reduced, the kinetics of the nucleation and growth processes also are greatly reduced, and a crystalline precipitate can be formed, since the growth species have time to order on particle surfaces."